Selectivity of clientele in finnish private early childhood education and care - Ville Ruutiainen; Maarit Alasuutari; Kirsti Karila (Taylor & Francis Group, 2021)
In accordance with the Nordic welfare model, the Finnish early childhood education and care (ECEC) system has traditionally been based on public provision and the idea of universalism. However, over the last twenty years the ECEC system has undergone market-oriented reforms. As a result, the share of private for-profit ECEC provision has grown significantly. By applying impression management theory, this qualitative research examines how representatives of private ECEC providers describe the selection and selectivity of their clientele and how they aim at managing the impression they convey through their descriptions. The study shows how three different mechanisms of selectivity are produced and legitimized in the interview talk. Furthermore, the study makes visible the cultural assumptions and expectations related to private ECEC provision and the potential selectivity it produces.